THE USE OF ARABIC STORY TEXT BASED MEDIA TO IMPROVE THE SPEAKING SKILLS OF TEN TH GRADE STUDENTS AT MADRASAH ALIYAH NURUL AMAL KUALA - Sari, Ayu Muli; Zulheddi, Zulheddi (Universitas Islam Negeri Sumatera Utara Medan, 2024)
This research is motivated by arabic language learning based on arabic story texts which aims to improve students’ speaking skills. The use of story text-based media to improve students’ speaking skills, and inappropriate method factors can cause students to experiemce learning difficulties resulting in low student learning outcomes. In thisstudy, researchers useb vocabulary reading tests and reading testsusing arabic texts. The purpose of this study was to determine students’ abilities in arabic language learing carried out by reading using arabic. The type of research used was field research, namely research conducted directly with researchers through interviews to obtain the results of prepared question. From the results of the study, researchers concluded that through the use of arabic vocabulary learning and arabictexts, students’speaking skills can be fluent, especially in arabic language learning and students can focus more on learning.